How Do Audit Capacity Stress Affect Audit Quality? The Mediating Mechanism of Due Professional Care - Abdul Hamid; Farhanah Murniasih (Universitas Muhammadiyah Prof. DR HAMKA., 2025)
This study aims to investigate whether due professional care mediates the relationship between audit capacity stress and audit quality. A quantitative approach was applied using survey data collected from 105 auditors working in Jakarta, Indonesia. Hypotheses were tested using the Hayes’ PROCESS Macro (Model 4) to test direct and indirect effects. The results indicate that audit capacity stress positively influences due professional care, suggesting a compensatory discipline effect whereby increased pressure stimulates greater auditor vigilance. Due professional care, in turn, has a significant positive effect on audit quality. Mediation analysis further reveals that due professional care partially mediates the relationship between audit capacity stress and audit quality, implying that heightened diligence can mitigate some adverse effects of stress, although excessive workload may still impair quality through other behavioral mechanisms such as fatigue or distraction. Theoretically, this study contributes to behavioral auditing literature by identifying due professional care as a key cognitive pathway linking stress and quality. Practically, the findings highlight the importance for audit firms to balance workload demands with effective supervision to sustain audit quality, particularly during peak audit periods.